2018
DOI: 10.1111/aphw.12147
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Depressive Symptoms, and Maternal Self‐Efficacy in First‐Time Mothers: Modelling and Predicting Change across the First Six Months of Motherhood

Abstract: Background First‐time mothers commonly experience stress and depressive symptoms in the postpartum period. Maternal self‐efficacy has been shown to be an important protective factor against these experiences; however, research on the dynamic nature of stress, depressive symptoms, and maternal self‐efficacy is limited. The aim of this study was to document changes in these psychological factors among first‐time mothers, and determine how early maternal self‐efficacy perceptions may predict change in stress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 56 publications
9
44
0
Order By: Relevance
“…Moreover, we found an increase over time in maternal self-efficacy in both study groups. This is consistent with the existing literature [65,66]: infants' demands become more predictable as they grow older, providing the opportunity to increase the mother's ability to successfully perform childcare tasks. However, we found that Be a Mom did not have a significant impact on the maternal self-efficacy of low-risk women.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, we found an increase over time in maternal self-efficacy in both study groups. This is consistent with the existing literature [65,66]: infants' demands become more predictable as they grow older, providing the opportunity to increase the mother's ability to successfully perform childcare tasks. However, we found that Be a Mom did not have a significant impact on the maternal self-efficacy of low-risk women.…”
Section: Discussionsupporting
confidence: 90%
“…11 and Barnard. 12,15 Also, similar to this study, previous studies have found that mothers who are more experienced have higher levels of maternal responsiveness. 15,26 Most of the mothers who have previous experience feel confident in reading their infant's cues such as the need to feed, be held or comforted, or play.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, it was found that mothers who did not have any prior experience in caring for a child showed lower maternal responsiveness compared with those who had already had a child. This is in line with Law et al, who conducted a qualitative study on motherhood difficulties and revealed that mothers without experience require more guidance and support on how to understand the cues shown by their babies to assist them in developing more confidence in their roles as a mother 11 . These findings underpin the importance of providing training for new mothers, such as ‘Promoting the First Relationship’ and ‘Baby Cues’ workshop programmes.…”
Section: Discussionsupporting
confidence: 83%
“…Considerable evidence exists that links maternal self-efficacy to women's psychological and child health outcomes. For example, research has illustrated that low maternal self-efficacy is linked to an increased risk of postpartum depression and maternal stress (Leahy-Warren and McCarthy 2011; Law et al 2019), poorer maternal bonding (Gharaibeh & Hamlan, 2012) and in some cases child neglect (Garay-Gordovil, 2013). A recent systematic review by Albanese, Russo and Geller (2019) suggests that parental self-efficacy may impact parent-child attachment too as a result of the level of support they feel they have from their partner (Casse, Oosterman & Schuengel, 2016), that it may mediate between internalized stigma and postpartum depression (Mickelson, Biehle, Chong & Gordon, 2017), and to child development such that low parental self-efficacy has been associated with increased child hospitalizations (Holland, Yoo, Kitzman, Chaudron, Szilagyi & Temkin-Greener, 2011).…”
Section: Introductionmentioning
confidence: 99%